Analisis Strategi dan Kunci Keberhasilan Lembaga Pendidikan Islam - Robi’ul Afif Nurul ‘Aini (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
The purpose of this study is to understand the Strategy Analysis and the Key to the Success of Islamic Education Institutions. This study discusses various types of strategy analysis that can be done in Islamic Education Institutions so that they become competitive, quality and successful Educational Institutions. The method used to achieve the objectives of writing is literature study and discussion with friends. Data was obtained from the results of the search and literature review of the strategies and keys to the success of Islamic Education Institutions. Based on the results of the study, it can be concluded: (1) Definition of Strategy Analysis, namely careful action planning in achieving and evaluating the desired goals and common goals. (2) Strategy Analysis that can be done in Islamic Education Institutions, namely by way of External Environmental Analysis (ALE) and by analysis of Internal Environment (ALI). (3)One of the Strategic Analysis Models in Islamic Education Institutions is a SWOT analysis model, TOWS analysis or Ballance Scored Card.(4) For the success of Islamic education institutions it should be pursued by several layered strategies, from internal business, as well as external ones.